2021
DOI: 10.1002/cncy.22505
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐institutional study of salivary gland cytopathology: Application of the Milan System for Reporting Salivary Gland Cytopathology in Japan

Abstract: BACKGROUND:The Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) is a risk-stratification reporting system that was introduced in 2018. The objective of this multi-institutional study was to evaluate the utility of the MSRSGC in Japan. METHODS: In total, 1608 fine-needle aspiration samples with matching histologic diagnoses were retrieved from 12 large institutions in Japan. The diagnostic categories of the MSRSGC were assigned prospectively or retrospectively, and the results were compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…Only SUMP cases with available glass slides for review and subsequent surgical resection were included. Among the 9938 salivary gland FNAs, 742 cases (7.4%) were classified as SUMP, which is comparable to the diagnostic rate reported in other large studies 13‐18 . Of these 742 cases, 329 (62.7%) had glass slides available for cytology review and surgical follow‐up.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Only SUMP cases with available glass slides for review and subsequent surgical resection were included. Among the 9938 salivary gland FNAs, 742 cases (7.4%) were classified as SUMP, which is comparable to the diagnostic rate reported in other large studies 13‐18 . Of these 742 cases, 329 (62.7%) had glass slides available for cytology review and surgical follow‐up.…”
Section: Discussionsupporting
confidence: 66%
“…Among the 9938 salivary gland FNAs, 742 cases (7.4%) were classified as SUMP, which is comparable to the diagnostic rate reported in other large studies. [13][14][15][16][17][18] Of these 742 cases, 329 (62.7%) had glass slides available for cytology review and surgical follow-up. The overall ROM for SUMP was 40.4%, higher than the estimation of 35% by the MSRSGC, but within the range of 39.4% and 42% reported in recent comprehensive and systematic reviews of the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review yielded 50 studies that reported FROMs using MSRSGC (Table 3). 8,15–58 The FROM for ND FNAs was 15.7% ( n = 208/1320), which was significantly lower than the 24.9% ( n = 2645/10611) FROM for all‐comers ( p < .001). There were 32 studies that also included the overall numbers of FNA for each category.…”
Section: Resultsmentioning
confidence: 82%
“…In contrast to this low malignancy risk, MSRSGC estimates the general ROM in nondiagnostic aspirates to be approximately 25% and recommends repeat FNA, imaging studies such as contrast‐enhanced CT/MRI, alternative biopsy approaches, or surgery 18 . Recent studies with large number of cases reporting on the application of MSRSGC have shown variable ROMs for the nondiagnostic category, ranging from 0% to 20% 17,19,21‐27 . These case series, together with 2 minimally overlapping meta‐analyses, 17,21 are summarized in Table 6.…”
Section: Discussionmentioning
confidence: 99%
“…18 Recent studies with large number of cases reporting on the application of MSRSGC have shown variable ROMs for the nondiagnostic category, ranging from 0% to 20%. 17,19,[21][22][23][24][25][26][27] These case series, together with 2 minimally overlapping meta-analyses, 17,21 are summarized in Table 6. Only studies that incorporated at least 300 total FNAs with at least 100 histologic follow-up were included in this summary.…”
Section: Cancer Cytopathology August 2022mentioning
confidence: 99%